Are Phthalate Exposure Related to Oxidative Stress in Children and Adolescents with Asthma? A Cumulative Risk Assessment Approach - Po-Chin Huang; Po-Keng Cheng; Hsin-Chang Chen; Ivy Shiue; Wan-Ting Chang; Hsin-I Huang; Jung-Wei Chang; I-Jen Wang (MDPI AG, 2022)
Childhood asthma has become one of the most common chronic diseases in children and adolescents. However, few case-control studies investigating the relationship between phthalate exposure and asthma in children and adolescents have been conducted, especially in Asia. Therefore, we assessed the potential associations between phthalate exposure and asthma among children and adolescents in Taiwan. Because various demographic and environmental variables may influence the incidence and prognosis of asthma, we performed a case-control study with propensity score matching. Out of 615 Childhood Environment and Allergic Diseases Study participants, we conditionally matched 41 children with clinically diagnosed asthma with 111 controls. We then analyzed 11 phthalate metabolites by using liquid chromatography with tandem mass spectrometry. Compared with the control group, the median urinary phthalate levels for most phthalate metabolites in the case group were slightly increased, including monomethyl phthalate, mono-n-butyl phthalate, monobenzyl phthalate, monoethylhexyl phthalate, mono-(2-ethyl-5-hydroxyhexyl) phthalate, mono-(2-ethyl-5-oxohexyl) phthalate, mono-(2-ethyl-5-carboxypentyl) phthalate, and mono-(2-carboxymethylhexyl) phthalate. Hence, our results suggest that phthalate exposure may be associated with the development of asthma. In addition, prenatal environmental factors, such as active or passive smoking during pregnancy, may increase the risk of asthma.